Web Browser Vulnerabilities and Weakness Descriptive Analysis: Is it Chrome Keep Dominant? - Fajar, Abdullah; Yazid, Setiadi; ., .; ., . (International Journal of Engineering and Technology, 2018)
Web Browser play the important mandatory role in accessing the application through the internet and may carry malicious content to the system henceÂ threatening the system from the attacker. Google Chrome is one of popular browser since released on 2008 as one of product of Chromium Project at Google. Chrome is fourth ranking in Common Vulnerabilities Enumeration website and the first ranking among browser that have most of vulnerabilities reported. This paper describe a Descriptive analysis of weakness and vulnerabilities of Chrome browser. The analysis use comparison approach to other popular browser such as Safari and Firefox. The analysis also use main reference and database from mitre.org which have common weakness enumeration database and scoring system calculation for vulnerability. This work cover responsiveness rate among them regarding weakness and vulnerabilities update duration and severity rate. The validation has performed using Descriptive test regarding weakness and vulnerability behavior. According to Architectural, Development and Research Conceptual weakness reported, the browsers has not significantly indicate the difference except between Chrome and Firefox in research conceptual weakness. The severity of browser vulnerabilities shown by Firefox and the best responsiveness to update browser weakness shown by Chrome, followed by Safari. Using Descriptive analysis, Chrome will keep dominant against the other browser, while Firefox and Safari potentially become unpopular such as Internet Explorer for upcoming time.Â